2017
DOI: 10.1007/s12020-017-1484-1
|View full text |Cite
|
Sign up to set email alerts
|

Should subcentimeter non-invasive encapsulated, follicular variant of papillary thyroid carcinoma be included in the noninvasive follicular thyroid neoplasm with papillary-like nuclear features category?

Abstract: Papillary thyroid microcarcinoma, NI-EFV, when stringently selected for, lacks metastasis at presentation and follows an extremely indolent clinical course, even when treated conservatively without RAI therapy. Provided stringent inclusion criteria are met, classification of subcentimeter mPTC, NI-EFV as NIFTP should be considered in order to avoid overtreatment of these biologically indolent lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 31 publications
1
32
0
1
Order By: Relevance
“…These and many other studies, including those with a smaller number of cases, confirm that the application of strict criteria for the diagnosis of NIFTP means that metastasis and BRAF mutations are not observed (13,91,92). Moreover, the available data indicate that both large NIFTPs (with a diameter ≥4 cm) and tumours with a diameter ≤1 cm that meet the NIFTP criteria (not included in the original study because of limited or lack of supportive data) do not differ from their 'average size' counterparts and show exceptionally indolent behaviour (93,94,95,96).…”
Section: Doubts Concerning the Indolent Behaviour Of Niftpmentioning
confidence: 71%
“…These and many other studies, including those with a smaller number of cases, confirm that the application of strict criteria for the diagnosis of NIFTP means that metastasis and BRAF mutations are not observed (13,91,92). Moreover, the available data indicate that both large NIFTPs (with a diameter ≥4 cm) and tumours with a diameter ≤1 cm that meet the NIFTP criteria (not included in the original study because of limited or lack of supportive data) do not differ from their 'average size' counterparts and show exceptionally indolent behaviour (93,94,95,96).…”
Section: Doubts Concerning the Indolent Behaviour Of Niftpmentioning
confidence: 71%
“…The size of the tumor does not constitute a criterion for the diagnosis of NIFTP (Nikiforov et al 2018), although some cases require greater care and time-consuming evaluation to ensure the absence of excluding findings. Reviewing 250 patients with subcentimeter NIFTP from nine studies (Thompson 2016, Can et al 2017, Hahn et al 2017, Kwon et al 2017, Johnson & Sadow 2018, Mainthia et al 2018, Rosario 2018c, Shafique et al 2018, Xu et al 2018, without associated PTC, we found only two patients with micrometastases <2 mm in a single lymph node in the central compartment, none with distant metastases and no case of recurrence. In addition, reviewing 265 patients with NIFTP ≥4 cm (Thompson 2016, Golding et al 2017, Kwon et al 2017, Rosario 2017b, Xu et al 2017a, Chereau et al 2019, Kim et al 2018b, Mainthia et al 2018, Parente et al 2018, excluding cases with associated PTC, we did not identify any patients with lymph node metastases (LNM), only one with pulmonary metastases and no case of recurrence.…”
Section: Diagnosis Of Niftpmentioning
confidence: 89%
“…Cases without initial agreement were shown at a multihead microscope to generate a consensus diagnosis. Subcentimeter nodules showing morphologic features consistent with NIFTP were still classified as such despite the size criterion …”
Section: Methodsmentioning
confidence: 99%
“…Subcentimeter nodules showing morphologic features consistent with NIFTP were still classified as such despite the size criterion. 31,32…”
Section: Reclassification Of Niftpmentioning
confidence: 99%